Rancangan Geometri Rencana Lereng Akhir Waste Dump terhadap Displacment Batuan Dasar Area Waste Dump PT X Kecamatan Palimanan, Kabupaten Cirebon, Provinsi Jawa Barat - Rana Antariksa D (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. PT X is a company engaged in the cement factory industry in West Java that uses an open-pit mining system with limestone mining. X is planning the location of waste dump placement using the in-pit dump method, so a safe and efficient final slope design is needed. For optimal stockpiling activities, slope geometry planning on the waste material dump needs to be carried out slope stability analysis. Slope stability is influenced by slope height, slope angle, rock mass strength, rock type, and groundwater level. The purpose of this research is to find out whether or not a slope is stably displayed in the Safety Factor (FK) value. Analysis process is carried out using the Finite Element Method and the Boundary Equilibrium Method. The analysis was carried out on bedrock and pile material. Analysis of bedrock using Finite Element Method in the Goa area in Sections A - B and C - D obtained SRF values ​​of 4.6 and 16 with a total displacement of 13,771 m and 6 m. In the area of ​​Mount Bindis Section E - F and G - H obtained SRF values ​​of 2.5 and 4.75 with a total displacement of 11.8 m and 3 m. Analysis of the embankment material in the Goa In areas with Sections A - B and C - D FK values ​​obtained = 2.11 and 1.56 and for Section C - D FK 2.62 and 1.94. In the Mount Bindis Area with sections E - F and G - H FK values ​​= 1.59 and for Section G - H FK values ​​= 2.31 and 1.57. The disposal obtained the amount of volume that will be accommodated in each area of ​​11,175,191.19 LCM and 74,749,919.45 LCM. Abstrak. PT X adalah perusahaan yang bergerak di industri pabrik semen di Jawa Barat yang menggunakan sistem penambangan terbuka dengan penambangan batu kapur. X sedang merencanakan lokasi penempatan pembuangan limbah dengan menggunakan metode pembuangan di dalam pit, sehingga diperlukan desain lereng akhir yang aman dan efisien. Untuk kegiatan penimbunan yang optimal, perencanaan geometri lereng pada tempat pembuangan bahan limbah perlu dilakukan analisis stabilitas lereng. Stabilitas lereng dipengaruhi oleh ketinggian lereng, sudut lereng, kekuatan massa batuan, jenis batuan, dan tingkat air tanah. Tujuan dari penelitian ini adalah untuk mengetahui apakah kemiringan secara stabil ditampilkan dalam nilai Safety Factor (FK). Proses analisis dilakukan dengan menggunakan Metode Elemen Hingga dan Metode Kesetaraan Batas. Analisis dilakukan pada material batuan dasar dan tiang pancang. Analisis batuan dasar menggunakan Metode Elemen Hingga di daerah Goa di Bagian A - B dan C - D memperoleh nilai SRF 4,6 dan 16 dengan total perpindahan 13,771 m dan 6 m. Di daerah Gunung Bindis Bagian E - F dan G - H diperoleh nilai SRF 2,5 dan 4,75 dengan total perpindahan 11,8 m dan 3 m. Analisis bahan timbunan di Goa Di daerah dengan Bagian A - B dan C - D nilai FK diperoleh = 2.11 dan 1.56 dan untuk Bagian C - D FK 2.62 dan 1.94. Di Wilayah Gunung Bindis dengan bagian E - F dan G - H nilai FK = 1,59 dan untuk Bagian G - H nilai FK = 2,31 dan 1,57. Pembuangan memperoleh jumlah volume yang akan ditampung di masing-masing area 11.175.191 LCM dan 74.749.919,45 LCM.